Framework for Performance Analysis of 10 Sharia Commercial Banks using CAMELS and PLS approaches compared to 10 Conventional Commercial Banks in Indonesia - R., A. E. Virgana Targa Sapanji; Syarif, Nurrohman; Sunaryo Mukhlas, Oyo; Anton Athoillah, Mohamad (International Journal of Psychosocial Rehabilitation, 2020)
Sharia Commercial Bank has a noble task of facilitating the public to be able to transact with banks in ways that are blessed by Allah Subhanahu wa ta'ala, which has justified the sale and prohibition of usury, as stated in His Word Al Qur ' an Al-Baqarah verse 275, this research will conduct an analysis of information related to the level of Performance Index of 10 Sharia Commercial Banks with CAMELS and PLS approaches compared to 10 Conventional Commercial Banks in Indonesia, and in this study will look for significant differences between bank performance Islamic banks and conventional commercial banks in Indonesia, and in particular significant differences between CAR, NPF / NPL, ROA, ROE, OER / BOPO and FDR / LDR in Islamic commercial banks and conventional banks in Indonesia, with a statistical least square approach ( PLS) - structure equation modeling (SEM).